Analisis Dampak Perubahan UU Pajak Penghasilan terhadap Besarnya Pajak Penghasilan pada PT JAJ - Dewi, Maya Safira; Setiawati, Hana (Binus Business Review, 2011)
One of company aims is improve company value by minimize tax burden that must paid. Nevertheless, for minimaze tax burden is referred must in accordance with Indonesia Tax Law. Reason and writer target is select this is because to analyse how far PT JAJ comprehends and deepens Law that go into effect in Indonesia and how far PT JAJ obeys its taxation obligation and give direct best solution can be applied to the problem that faced PT JAJ. Where the shoe pinches in research this is how PT JAJ executes its taxation obligation bases regulation and taxation rule that go into effect and keep abreast of regulation that effected. Research Method that used is research explanatory that have the character of qualitative in form of case study. Research that conducted is analysis to newest applying of taxation regulation, fiscal correction and reconciliation to the company income statement, calculation analysis for tax credit and decrease of company plant asset. In this research, PT JAJ has went by the book that go into effect. Nevertheless, there still some mistakes in conducting calculation, until tax liability that ought to remit differ from tax liability that counted company.From research result above, a large part of causes its is existence of inadvertence in counting tax liability company and tax consultant that has not yet fully obeyed taxation obligation to axation.Â